A new species of Albatrellus sensu stricto (Albatrellaceae, Russuales) from China - Zhou, Hong-Min; Wu, Ying-Da; Dai, Yu-Cheng (Phytotaxa, 2021)
Based on morphological and molecular data, a new species of Albatrellus sensu stricto, A. alpinus sp. nov., is described from Yunnan Province of southwestern China. Albatrellus alpinus is characterized by a buff to pale yellow pileal surface, simple septate hyphae, yellow and shapeless oily substance present in all hyphae but seldom in tramal hyphae, and small amyloid basidiospores. Phylogenetic analyses based on the nuclear ribosomal internal transcribed spacer (nrITS) and the large subunit of the nuclear ribosomal RNA gene (nLSU) indicated that the new species is nested within Albatrellus sensu stricto. A key to the Chinese species of Albatrellus sensu stricto is provided.